(untitled) (American Journal of Islam and Society, 1993)
In addressing the situation of Muslim communities in Britain, it is apparent that one of the major frameworks for understanding their situation has been the notion of "Citizenship," for citizenship is a means of identifying critical aspects of the relationship between the individual and the state. Following Bottomore (1992), we may make a useful distinction between "formal" and "substantive" citizenship: the former being Simply defined as "membemhip in a nation state" and the latter as "an array of civil, political, and especially social rights, involving also some kind of participation in the business of government’’ (ibid.). There are a number of salient points that should be made in relation to examining the implications of this distinction. First, we may note that the legal definition of citizenship is always informed by the cultural and ethnic agendas historically rooted in the foundation myths of each nationstate. Thus in France, for example, just as the revolutionary iconography of the Tricolor, Marianne, and Liberty, Equality, and Fratemity continue to serve contemporary national sentiments (Hobsbawm 1983), so today French legal framing of formal citizenship is infused with its revolutionary roots: La tradition centraliste francaise interdit la reconnaissance dans l’espace public des ’communautes’, au sens oii elles existent au Wtats-Unis. (Schnapper 1990). Consequently, in France neither ethnicity nor religion are formally relevant in determining access to citizenship ...